2015
DOI: 10.1007/978-3-662-47989-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Multi-key Security: The Even-Mansour Construction Revisited

Abstract: Abstract. At ASIACRYPT 1991, Even and Mansour introduced a block cipher construction based on a single permutation. Their construction has since been lauded for its simplicity, yet also criticized for not providing the same security as other block ciphers against generic attacks. In this paper, we prove that if a small number of plaintexts are encrypted under multiple independent keys, the Even-Mansour construction surprisingly offers similar security as an ideal block cipher with the same block and key size. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Andreeva et al [3] and Mouha and Luykx [64] considered one round of Even-Mansour in the multi-key setting, and showed that similar results are achieved.…”
Section: Iterated Even-mansourmentioning
confidence: 84%
See 2 more Smart Citations
“…Andreeva et al [3] and Mouha and Luykx [64] considered one round of Even-Mansour in the multi-key setting, and showed that similar results are achieved.…”
Section: Iterated Even-mansourmentioning
confidence: 84%
“…3. While earlier definitions, including Mouha and Luykx [64], only considered independent, uniformly generated keys, we introduce KDFs in the definition of multi-key security, and say that the combination of a blockcipher with KDF is secure if it is indistinguishable from uniform random permutations.…”
Section: Linking Multi-key Security With Tweakable Blockciphersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Shrimpton and Terashima [49] introduced a new model in order to bridge gaps between standard and ideal model bounds to analyze settings where the standard model bounds provide little assurance of security, like the multi-key setting. Other research on security of block ciphers in the multi-key setting includes the works by Mouha and Luykx [39], Tessaro [51], and Fouque et al [24]. However, there is no systematic treatment of the problem like that provided in our work.…”
Section: Further Related Workmentioning
confidence: 51%
“…Andreeva et al [2] considered the security of the outer-and inner-keyed sponge in the multi-target setting, a proof which internally featured a security analysis of the Even-Mansour blockcipher in the multi-target setting. The direction of multi-target security got subsequently popularized by Mouha and Luykx [40], leading to various multi-target security results [4,33] with security bounds (almost) independent of the number of targets involved.…”
Section: Multi-target Securitymentioning
confidence: 99%